International Multi-Conference on Systems, Sygnals &Amp; Devices 2012
DOI: 10.1109/ssd.2012.6197972
|View full text |Cite
|
Sign up to set email alerts
|

Design criteria and levelized costs of electricity for photovoltaic power plants at different global locations

Abstract: this research deals with design criteria for photovoltaic power plants at different global locations. The ground-mounted systems with an installed power greater than 500 kW are equipped with central inverters and located in the countries of Italy, Canada, Israel, Libya and China. The analysis focuses the effects of ambient temperature and radiation on the behavior of the overall system, as well as of the individual system components and of the electricity production costs of defined photovoltaic power plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…In order to properly compare all the configurations, the LCOE is evaluated in this section [26], [27]. It takes into account both the extracted energy over the lifetime of the plant and the life cycle cost of the studied structures:…”
Section: B Levelized Cost Of Energymentioning
confidence: 99%
“…In order to properly compare all the configurations, the LCOE is evaluated in this section [26], [27]. It takes into account both the extracted energy over the lifetime of the plant and the life cycle cost of the studied structures:…”
Section: B Levelized Cost Of Energymentioning
confidence: 99%
“…Furthermore, future generation costs of solar electricity are expected to decrease in coming decades, due to the law of mass production and learning from experience, whereas the price of fossil fuels will probably increase [18]. Some studies [17,19,20] have reported that grid parity has been reached in some Italian areas according to the specific size of the PV system, due mainly to high irradiation levels, expensive grid electricity prices and cost-competitive installations of PV systems. Moreover, grid parity is more readily achieved in insular systems, primarily thanks to the higher selling prices of the produced energy [21].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, as reported in other studies [19,[49][50][51], PV electricity costs have been calculated by means of LCOE, because high electricity generating costs have represented the main obstacle to more widespread deployment of PV technologies [52], in order to compare the generation costs of electricity by conventional and PV plants [53].…”
Section: Introductionmentioning
confidence: 99%